Filme de partículas de cálcio: tecnologia aplicada para superação do estresse abiótico em plantas de abóbora cv Mini Jack e batata-doce cv Ourinho - Fontes, Pryanka Thuyra Nascimento (2023)
Given the increase in global temperature, light intensity, and irregular rainfall, yield has declined in several crops, with a direct impact on food security. Thus, in order to mitigate the negative effects of abiotic stress, researchers are looking for sustainable technologies that act directly to reduce leaf photoinhibition and increase photosynthesis, ensuring increased production and fruit quality. In this context, a film of CaO particles becomes a viable alternative for photoprotection of plants. The CaO film, in addition to being a readily available material derived from renewable sources of calcium, showed beneficial results for photoprotection in bean, tomato, and coffee crops. Therefore, the objective of this study was to evaluate the photoprotective effect of a CaO particle film on pumpkin cv. Mini Jack in two years of cultivation and on sweet potato cv. Ourinho under different irrigation depths. Anatomical parameters of the leaves and physiological, morpho-agronomic, and qualitative parameters of the fruit (pumpkin) and roots (sweet potato) were evaluated. Our results showed that the application of the CaO particle film at a concentration of 5.0% promoted an increase in chlorophyll levels and parameters related to the efficiency of photosystem II, in addition to reducing energy dissipation in the leaves of pumpkin cv. Mini Jack, resulting in increased yield in the two years of cultivation. In addition, at this concentration, pumpkin fruit showed better qualitative traits. For the sweet potato crop, the application of the CaO film enhanced the physiological parameters, regardless of the irrigation depth applied, which was reflected in an increase in the photosynthetic rate and in the photosystem II efficiency levels. It also allowed maintenance of the organizational structure of the leaves when subjected to water restriction. The use of particle film on sweet potato increased the yield of plants that were not under restriction and allowed maintenance of the vegetative part of the stressed plants. The qualitative parameters of the roots also improved. Therefore, the application of particle film to the crops under evaluation can be a sustainable alternative to mitigate the effects of abiotic stress, considering the satisfactory results for photoprotection of plants, increased yield, and product quality.